2007
DOI: 10.1124/jpet.107.132662
|View full text |Cite
|
Sign up to set email alerts
|

Plitidepsin Has a Dual Effect Inhibiting Cell Cycle and Inducing Apoptosis via Rac1/c-Jun NH2-Terminal Kinase Activation in Human Melanoma Cells

Abstract: Melanoma is the most aggressive skin cancer and a serious health problem worldwide because of its increasing incidence and the lack of satisfactory chemotherapy for late stages of the disease. The marine depsipeptide Aplidin (plitidepsin) is an antitumoral agent under phase II clinical development against several neoplasias, including melanoma. We report that plitidepsin has a dual effect on the human SK-MEL-28 and UACC-257 melanoma cell lines; at low concentrations (Յ45 nM), it inhibits the cell cycle by indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 37 publications
2
35
0
Order By: Relevance
“…It has been shown that Akt regulates cell cycle by controlling of cyclins and CDK inhibitors (49)(50)(51)(52). In addition, JNK is involved in cell-cycle progression and mediates G 2 -M phase cell-cycle arrest in different tumor cells (53)(54)(55)(56)(57)(58). As both, decreased phosphorylation of Akt and increased phosphorylation of JNK are evident after treatment with 1, these signaling cascades may be responsible for the observed G 2 -M arrest upon treatment.…”
Section: Discussionmentioning
confidence: 98%
“…It has been shown that Akt regulates cell cycle by controlling of cyclins and CDK inhibitors (49)(50)(51)(52). In addition, JNK is involved in cell-cycle progression and mediates G 2 -M phase cell-cycle arrest in different tumor cells (53)(54)(55)(56)(57)(58). As both, decreased phosphorylation of Akt and increased phosphorylation of JNK are evident after treatment with 1, these signaling cascades may be responsible for the observed G 2 -M arrest upon treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Many investigations have suggested that the expression level of RhoGDI-␣ closely modulates the JNK activity, which is strongly related to the apoptotic cell death (Muñoz-Alonso et al, 2008;Park et al, 2009). In this study we found that Fr-6 could knockdown the RhoGDI-␣ gene expression in human A549 cells and JNK inhibitor SP600125 could abrogate Fr-6-mediated JNK activation and cell death.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies have shown that plitidepsin induces JNK phosphorylation in a variety of cultured solid and hematological cancer cell lines [3,4,5,9,11,15]. Given the advanced clinical development of plitidepsin in multiple myeloma and leukemia, we have evaluated the effect of plitidepsin on the viability and the level of JNK phosphorylation in a panel of these different cancer cell types.…”
Section: Resultsmentioning
confidence: 99%
“…In cultured cells from solid tumors, plitidepsin induces dose-dependent cell cycle arrest or an acute apoptotic process due primarily to the sustained activation of c-Jun N -terminal kinase (JNK) as revealed by an increased level of phosphorylation [2,3]. Plitidepsin also activates other kinases such as the epidermal growth factor receptor, protein kinase C-δ and the extracellularly regulated and p38 mitogen-activated protein kinases (ERK, p38MAPK) in a cell-dependent context [4,5].…”
Section: Introductionmentioning
confidence: 99%